Understanding Consumer Intention to Use Go-Pay: Development and Testing of Technology Acceptance Models for Consumers - Purwanto, Sugeng; Hartini, Sri; Premananto, Gancar C (STIE PGRI Dewantara Jombang, 2019)
The purpose of this study is to develop and test an integrated model of technology acceptance to determine the Intention of consumers to use e-wallet. The object used is the go-pay application wich is the relatively new technology products in Indonesia. Modeling in this study is integrating the Technology Acceotabce Model (TAM) model by involving affective factors namely Pleasure, Arousal, and Dominance (PAD) theory, and prior experience variables as a direct effect on perceiveid usefulness and Attitude toward usage, then its effect on adoption Intention. The sample in this study is millennial people age with a total sample of 270 respondents, analysis techniques using SmarPLS. The results of this study indicate that perceived usefulness, perceived easy of use, Pleasure, and Arousal have a positive effect on Attitude and Intention to use go-pay, while prior experience supports perceived usefulness, but does not support Attitude, and Dominance does not support the Attitude of using go-pay.